Socioeconomic Determinants of Investment Intention in the Islamic Capital Market: Evidence from Lebong Regency, Indonesia - Winda Yuneri; Evan Stiawan; Yetti Afrida Indra (Fakultas Ekonomi dan Bisnis Islam _ IAIN Sultan Amai Gorontalo, 2026)
This study aims to analyze the influence of income, education level, occupation, and social environment on public investment interest in the Islamic capital market in Topos District, Lebong Regency, Bengkulu, Indonesia, Lebong Regency. This research employs a quantitative approach using survey methods through questionnaire distribution to respondents. The population of this study consists of productive-age community members in Topos District, Lebong Regency, Bengkulu, Indonesia, with a sample of 100 respondents selected using purposive sampling techniques. Data were collected using a Likert scale questionnaire and analyzed using multiple linear regression analysis to examine the relationship between the independent variables and investment interest. The results indicate that education level and the social environment have a positive and significant influence on public investment interest in the Islamic capital market. Higher educational attainment improves individuals’ understanding of financial concepts and investment opportunities, while supportive social interactions encourage individuals to participate in investment activities. Income and occupation do not significantly influence investment interest, suggesting that economic capacity alone does not necessarily determine individuals’ willingness to invest. The findings highlight that social and knowledge-related factors play a more important role than purely economic factors in shaping investment interest.